Question #080e7

1 Answer
Mar 10, 2017

Answer:

#x = 11#; #y = 87#

Explanation:

Given:
#y=x^2−3x−1#
#y=8x−1#

Since both of these equations on the right side are equal to #y# on the left side we can merge these two equations into:

#x^2−3x−1=8x−1#

Then, combine like terms:

#x^2=11x#

Divide each side by x, and you get #x=11#

You will need to continue on to solve for #y# by inserting your value for #x# into either of the #given# equations:

#y = 8x -1#
#y = 8(11) - 1#
#y = 88 -1#
#y = 87#

From here you can check your answer by substituting both of your values into the other #given# equation:

#y = x^2 - 3 x - 1#
#(87) = (11)^2 -3(11) -1#
#87 = 121 -33 -1#
87 = 87